MONITORING THE USE OF PERSONAL PROTECTIVE EQUIPMENT ON EMPLOYERS’ HEALTH AND SAFETY - Levi Anatolia S.M. Exposto; Manuel Fransisco; Terejinha R. Gonçalves; Angela L. Colo; Quintiliano F. Barros; Hernanio M.C. Costa; Rogerio Fontes (International Journal Labs, 2022)
Personal Protective Equipment (PPE) is a tool that has the ability to protect a person whose function is to isolate part or all of the body from potential hazards in the workplace. This PPE consists of mandatory equipment used by workers in accordance with work hazards and risks used to maintain the safety of workers as well as those around them. In developing countries such as Timor-Leste, the issue of occupational health and safety still seems to be something that has not received the maximum portion of attention. The aim is to know and understand the use of Personal Protective Equipment for the Occupational Health and Safety of Employees of the Auto Vision Aimutin Company, Dili. This research is qualitative research with an analytical descriptive approach that serves to describe or provide an overview of the object under study through data or samples that have been collected as they are without analyzing and making conclusions that apply to the public. The use of personal protective equipment (PPE) is very important for the health and safety of workers, while those who do not use personal protective equipment are at high risk of contracting disease in the work environment. The results of respondents' answers about occupational health and safety, occupational health, work safety, and personal protective equipment (PPE) are the majority of respondents answered strongly agree with the percentage value (100%), while to agree and strongly disagree respondents did not provide answers with a percentage value (0%).